2021
DOI: 10.1007/s40429-021-00377-5
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Based Treatment Approaches in the Field of Substance Use Disorders

Abstract: Purpose Substance use disorders (SUD) are burdening chronic conditions characterized by high relapse rates despite severe negative consequences. Substance-related cues that elicit craving by means of automatic physiological and behavioural responses have long been suggested to predict relapse. One major mechanism contributing to relapse behaviour are cue-induced behavioural approach tendencies towards the addictive agent. Recently, there has been an emerging interest in virtual reality (VR)-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
14
0
2
Order By: Relevance
“…A number of systematic reviews have examined the effectiveness of VR interventions on improving smoking, alcohol, physical activity and/or obesity risk factors [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] but none have focussed on nutrition. However, these reviews focus primarily on a single health risk behaviour [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], the outcome of cravings [ 20 , 21 , 22 ], a specific type of VR such as avatar-based studies [ 15 ], or included non-randomised controlled studies [ 20 ]. In relation to smoking tobacco, systematic reviews have shown promising results showing VR cue exposure therapy can be used to reduce cravings [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of systematic reviews have examined the effectiveness of VR interventions on improving smoking, alcohol, physical activity and/or obesity risk factors [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] but none have focussed on nutrition. However, these reviews focus primarily on a single health risk behaviour [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], the outcome of cravings [ 20 , 21 , 22 ], a specific type of VR such as avatar-based studies [ 15 ], or included non-randomised controlled studies [ 20 ]. In relation to smoking tobacco, systematic reviews have shown promising results showing VR cue exposure therapy can be used to reduce cravings [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these reviews [ 16 , 20 ] included studies with no control group, non-randomised studies, compared VR with VR comparators, or the review focused on the type of therapies delivered through VR and not the effectiveness of VR itself. Existing systematic reviews examining VR interventions and alcohol have focused on VR cue exposure therapy as a treatment for cravings, driving simulations, or training and not the effectiveness of VR on cessation of alcohol use/misuse [ 11 , 14 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die VR-Exposition mit suchtassoziierten Stimuli löste in mehreren Studien Craving bei Patienten mit Nikotin‑, Alkohol-, sowie Methamphetaminabhängigkeit aus, wobei zum Teil olfaktorische Reize zur Verstärkung eingesetzt wurden [ 40 ]. Die Wiederholung von Expositionen führte in mehreren Studien zu einer signifikanten Craving-Reduktion [ 27 , 42 ]. Bisher fehlen aber randomisierte kontrollierte Studien zur Wirksamkeit der VR-Anwendungen bezüglich Verbesserung von Abstinenzraten oder -dauern [ 27 , 42 ].…”
Section: Abhängigkeitserkrankungenunclassified